Mediating effect of intolerance of uncertainty in the relationship between coping styles with stress during pandemic (COVID-19) process and compulsive buying behavior - Çelik, Samet; Köse, Gözde Güsan (Elsevier Inc., 2021)
Novel CoronaVirus Disease (COVID-19) has begun to expand swiftly beyond all borders and turned into a global source of infection for humans in that all media corporations began to repeatedly share breaking news to release the latest data of all countries. The consequence of that has been a heightened level of anxiety among humans and opting for unorthodox consumption behaviors as consumers. In this study the attempt was to analyze human behaviors during the ongoing pandemic process from the perspective of psychology and marketing fields of science. In so doing, interrelation among anxiety, which surfaced because of Covid-19 pandemic, coping style with stress of individuals and compulsive purchase behavior has been explored. Based on these interrelations, a structural model was suggested. Findings of the research indicated that anxiety has high effect on the helpless approach dimension, which is one of the coping styles with stress; and that helpless approach alone has an effect on compulsive buying behavior. Besides, another objective of the study was to evaluate the mediating effect of intolerance of uncertainty between coping style with stress and compulsive buying behavior. That analysis evidenced that intolerance of uncertainty in such an interrelation had a partial mediating effect.
Keywords: Anxiety; Compulsive Buying Behavior; Intolerance for Uncertainty; Stress-Coping Strategy